2015
DOI: 10.3233/xst-140469
|View full text |Cite
|
Sign up to set email alerts
|

Clinical values of of gemstone spectral CT in diagnosing thyroid disease

Abstract: OBJECTIVE: To quantitatively evaluate the diagnostic value of gemstone spectral CT in thyroid disease. PATIENTS and METHODS: A total of 123 patients with thyroid diseases were enrolled in the retrospective study. All the patients underwent spectral CT scan, and 39 of them underwent dual-phase enhanced scan. Iodine concentration (IC) and normalized IC (NIC) were compared between benign and malignant nodules. The optimal threshold to predict malignancy was obtained by receiver operating characteristic curve (ROC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 24 publications
4
17
0
Order By: Relevance
“…To our knowledge, a few studies have addressed the relationship between the quantitative parameters derived from DECT and thyroid disease, for example, IC, effective atomic numbers (Z eff ), or spectral curve slopes of thyroid nodules. [23][24][25][26] Li et al first reported significant differences in IC, Z eff , or spectral curve slopes between malignant and benign thyroid nodules using non-enhanced CT images with 97 surgically removed thyroid nodule specimens (all P < .001). 23 Later, the same group suggested practical parameters regarding the regional characteristics of thyroid nodules, such as a threshold IC value for discriminating intranodular hemorrhage from the surrounding solid portion, which was not apparent by single-energy CT. 24 According to another study, both IC and normalized IC values were significantly lower in malignant nodules than benign nodules (P < .001); therefore, the thresholds for discrimination were determined to be about 0.68 mg/mL for IC and 0.38 mg/mL for normalized IC, with a sensitivity of 74.3%/76.9% and a specificity of 66.7%/80.0%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To our knowledge, a few studies have addressed the relationship between the quantitative parameters derived from DECT and thyroid disease, for example, IC, effective atomic numbers (Z eff ), or spectral curve slopes of thyroid nodules. [23][24][25][26] Li et al first reported significant differences in IC, Z eff , or spectral curve slopes between malignant and benign thyroid nodules using non-enhanced CT images with 97 surgically removed thyroid nodule specimens (all P < .001). 23 Later, the same group suggested practical parameters regarding the regional characteristics of thyroid nodules, such as a threshold IC value for discriminating intranodular hemorrhage from the surrounding solid portion, which was not apparent by single-energy CT. 24 According to another study, both IC and normalized IC values were significantly lower in malignant nodules than benign nodules (P < .001); therefore, the thresholds for discrimination were determined to be about 0.68 mg/mL for IC and 0.38 mg/mL for normalized IC, with a sensitivity of 74.3%/76.9% and a specificity of 66.7%/80.0%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…23 Later, the same group suggested practical parameters regarding the regional characteristics of thyroid nodules, such as a threshold IC value for discriminating intranodular hemorrhage from the surrounding solid portion, which was not apparent by single-energy CT. 24 According to another study, both IC and normalized IC values were significantly lower in malignant nodules than benign nodules (P < .001); therefore, the thresholds for discrimination were determined to be about 0.68 mg/mL for IC and 0.38 mg/mL for normalized IC, with a sensitivity of 74.3%/76.9% and a specificity of 66.7%/80.0%, respectively. 25 However, their diagnostic performances of IC varied substantially depending on the degree of contrast enhancement; therefore, the AUC of contrast-enhanced CT with a 33-to 36-second scan delay was greater than that of the non-enhanced images (0.88 vs 0.71), whereas normalized ICs obtained from relatively early scans, for example, 20-to 23-second scan delay, showed no difference between the 2 groups (P = 0.65). In this regard, scan delay would be important in determining the diagnostic performance of IC; moreover, sufficient tumor conspicuity must be required for accurate ROI drawing on the contrast-enhanced CT image.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations